1997
DOI: 10.1080/03637759709376402
|View full text |Cite
|
Sign up to set email alerts
|

Men's interactions with women after viewing sexually explicit films: Does degradation make a difference?

Abstract: Short-term exposure to nonviolent sexual media stimuli can produce cognitive changes in men, which, in turn, can affect their attitudes toward women. This study sought to build on past research by reliably distinguishing between (a) sexually explicit and non-sexual films and (b) sexually explicit films that are either degrading or non-degrading to women. We tested whether men's viewing of these materials affects their judgment of women in subsequent face-to-face interactions. Sex-typed and non sex-typed men (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Much of the past research on viewing SEM and relationships has been conducted in laboratories using experiments and random assignment (e.g., Glascock, 2005;Jansma et al, 1997; Kenrick et al, 2003). In contrast, the current study asked individuals about their own experiences with SEM and assessed how viewing SEM with one's romantic partner or on one's own was associated with key dimensions of relationship quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the past research on viewing SEM and relationships has been conducted in laboratories using experiments and random assignment (e.g., Glascock, 2005;Jansma et al, 1997; Kenrick et al, 2003). In contrast, the current study asked individuals about their own experiences with SEM and assessed how viewing SEM with one's romantic partner or on one's own was associated with key dimensions of relationship quality.…”
Section: Discussionmentioning
confidence: 99%
“…Linz, Donnerstein, and Penrod (1988) found that exposure to non-violent pornography did not increase men's judgments of women as sexual objects. Similarly, there is evidence that even watching explicitly degrading pornography does not change men's rating of women's intellectual competence, sexual interest, attractiveness, or permissiveness (Jansma, Linz, Mulac, & Imrich, 1997). Taken together, it appears that although some men may experience increases in negative opinions about women after exposure to SEM, not all men are affected in such negative ways.…”
Section: Introductionmentioning
confidence: 99%
“…In the aggregation of experimental research concerning the possible effects of exposure to traditional forms of pornography, sexual aggression and sex-related attitudes have been repeatedly treated as the dependent variables (e.g., Barak & Fisher, 1997;Barak, Fisher, Belfry, & Lashambe, 1999;Jansma, Linz, Mulac, & Imrich, 1997;Padgett, Brislin-Slutz, & Neal, 1989;Zillman & Weaver, 1989). However, as reviewed by Fisher and Barak (2001), studies exploring the influence of Internet pornography are very limited.…”
Section: Possible Impact Of Cyberpornography Usementioning
confidence: 99%
“…The cultural objectification of women exerts many negative impacts at the cultural level, including increased sexist attitudes toward women (Mundorf, Allen, D'Alessio, & Emmers-Sommer, 2007), increased violence against women (Hald, Malamuth, & Yuen, 2010), and decreased appraisals of women's competence (Jansma, Linz, Mulac, & Imrich, 1997). The cultural objectification of women also exerts a detrimental impact at the level of the self in exposed women, a construct referred to as self-objectification (Fredrickson & Roberts, 1997;Fredrickson, Roberts, Noll, Quinn, & Twenge, 1998).…”
Section: Consequences Of the Objectification Of Womenmentioning
confidence: 97%